PREVALENCE OF INFECTION OF ZOONOTIC POTENTIAL GASTROINTESTINAL WORM IN CAT IN DENPASAR CITY - Misa, Makrina Weni; Suratma, Nyoman Adi; Dwinata, I Made (Buletin Veteriner Udayana, 2022)
Cats as pets have their own charm because of their various body shapes, eyes and hair colors. However, cats are susceptible to disease, and even become a source of zoonoses for humans. There are several types of worm parasites that are often found in the digestive tract of cats such as Ancylostoma spp., Toxocara cati, Strongyloides spp . Dipylidium caninum and Spirometra which have high potential to cause zoonoses. The purpose of this study was to determine the prevalence of infection and the relationship with several factors (race, sex, age and maintenance management) to gastrointestinal worms that have zoonotic potential in cats in Denpasar City. The number of samples used in this study was 100 samples of cat feces and the data were analyzed by chi-square test. Samples were examined using the floating concentration method, with a saturated NaCl flotation agent. The results of the study found that the prevalence of Ancylostoma spp. was 8%, Toxocara cati was 10% and there was a mixed infection between the two of 19%. So, the overall percentage is 37%. Meanwhile, it is also known that there is a relationship between maintenance management and the prevalence of gastrointestinal helminth infections in cats. On the other hand, there is no relationship between race, sex, and age as risk factors with the prevalence of gastrointestinal worms.